(untitled) (Baghdad Science Journal, 2025)
The 4-(?-bromo acetyl)-4?-toluene sulfonanilide (2) was used as key intermediate to synthesize new heterocyclic compounds. This bromo compound was synthesized via sulfonation of amino group of p-amino acetophenone using Hinsburg method with 4-toluene sulfonyl chloride to form 4-acetyl-4?-toluene sulfonanilide (1) which is used as a starting material in this work. This compound was brominated to yield compound (2) which is used as a precursor to synthesize new five and seven membered heterocyclic compounds such as substituted 1,3-oxazoles (3,4), 1,3-thiazole derivatives (5-7), thiourea compounds (8a,b), 1,3-Thiazoline-2-thione compounds (9a-f) and 1,2,5-triazepine compounds (11a-d). The synthesized compounds were identified depending upon physical, FT-IR and UV spectroscopic data.